2007
DOI: 10.1093/aje/kwk118
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR15 Haplotype and Multiple Sclerosis: A HuGE Review

Abstract: An association between multiple sclerosis (MS) and the human leukocyte antigen (HLA) complex, a dense cluster of genes on the short arm of chromosome 6, was first noted over 30 years ago. In Caucasian populations of Northern European descent, the DR15 haplotype (DRB1*1501-DQA1*0102-DQB1*0602) has been hypothesized to be the primary HLA genetic susceptibility factor for MS. However, studies of other populations have produced varying results. Thus, the authors reviewed the literature for articles on the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
115
4
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(132 citation statements)
references
References 142 publications
9
115
4
4
Order By: Relevance
“…The present findings implicate immunoregulatory elements within the HLA Class II complex in the pathogenesis of IPF. These data are also consistent with the hypothesis that the development of IPF likely involves interactions between environmental agent(s) and genetic factors [34,35], a disease paradigm also common to many other disorders, notably including those caused by aberrant immune processes [19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The present findings implicate immunoregulatory elements within the HLA Class II complex in the pathogenesis of IPF. These data are also consistent with the hypothesis that the development of IPF likely involves interactions between environmental agent(s) and genetic factors [34,35], a disease paradigm also common to many other disorders, notably including those caused by aberrant immune processes [19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 87%
“…Two distinct mechanisms may account for the frequently observed associations between unique HLA polymorphisms and various disease syndromes [19][20][21][22][23][24]. First, HLA molecules are requisite effectors for presentations of peptide antigens to the Tcells that initiate adaptive immune responses, but each distinct HLA allele has a restricted peptide binding motif [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The strongest and the best characterized predisposing genetic factor for MS lies, as in many autoimmune diseases, in the major histocompatibility complex of chromosome 6: the HLA-DRB1*1501 allele. 2,3 Polymorphisms of other genes related to the immunological response, namely IL7R and IL2RA, also contribute, albeit more modestly, to the risk of suffering MS (odds ratio (OR) values: 1.18-1.34). [4][5][6][7] In Germans, 8 RR-MS is associated with deficiency of the A3 member of the leukocyte immunoglobulin (Ig)-like receptor family (LILRA3, CD85e), molecule earlier referred to as Ig-like transcript 6 (ILT6), leukocyte Ig-like receptor 4 (LIR-4) or HM43.…”
Section: Introductionmentioning
confidence: 99%
“…HLA genes have three groups: class I, class II, and class III. The present of antigens from outside of the cell to T-lymphocytes is the function of HLAs class II and it contains the classical alpha and beta chain genes including DP, DM, DOA, DOB, DQ , and DR. As Class II molecules can bind and present certain self-peptides, several studies indicated that HLAs class II have been associated to several autoimmune or immune mediated disorders, including MS [29]. An estimated 10-60% of the MS genetic risk appears to be conferred by the DR15 haplotype (DQB1*0602, DQA1*0102, DRB1*1501, DRB5*0101) [30].…”
Section: Introductionmentioning
confidence: 99%